Gamification development in virtual tour Cau Belayu tourism Village - Sarja, Ni Luh Ayu Kartika Yuniastari; Sarja, Ni Ketut Pradani Gayatri; Widana, I Putu Krisna Arta (Bulletin of Social Informatics Theory and Application, 2023)
The use of digital marketing is not only specifically for business processes but can also be utilized in the tourism sector. Tourist information, especially tourist villages, can be easily searched via the internet and social media. There is no need to use conventional promotional media, print brochures or advertisements in the mass media, which will cost a lot, especially for tourism village managers. Virtual tour is an example of digital promotional media that is currently developing because it can display real tourist destinations without having to come to the location in person. However, virtual tours only display static images or videos and do not interact with users or tourists other than information, this causes the virtual tour to not have a significant effect on tourist interest to visit in person. There is a need for further development of virtual tours to make it more attractive to tourists to visit, one way is by combining it with other technologies, namely gamification. This research develops a gamification application on a virtual tour for Cau Belayu Tabanan Tourism Village. By applying gamification to the virtual tourist village tour, it is hoped that tourists will be able to experience a more enjoyable and significant impact on tourist interest in visiting the Cau Belayu Tabanan tourist village directly. The research method used refers to the MDLC (Multimedia Development Life Cycle). The research method consists of the stages of concept, design, material collecting, assembly, testing and distribution. The results of this study are in the form of a gamification application in the virtual tour of the Cau Belayu Tabanan Tourism Village which has the main features, namely games, gamescores and game finishes.